Enzymeless biosensor based on β-NiS@rGO/Au nanocomposites for simultaneous detection of ascorbic acid, epinephrine and uric acid. Issue 99 (10th October 2016) - Muthukumaran, P.; Sumathi, C.; Wilson, J.; Ravi, G.
Abstract : In this study, marigold flower-like self-assembled β-NiS (nickel sulfide) nanosheets were grown on rGO (reduced graphene oxide) by a single-step hydrothermal process and then gold nanospheres (AuNS) were electrochemically deposited on the β-NiS@rGO nanostructures. Abstract : In this study, marigold flower-like self-assembled β-NiS (nickel sulfide) nanosheets were grown on rGO (reduced graphene oxide) by a single-step hydrothermal process and then gold nanospheres (AuNS) were electrochemically deposited on the β-NiS@rGO nanostructures. The β-NiS@rGO/AuNS hierarchical hybrid demonstrates excellent electrochemical activities for clinically important analytes such as AA (ascorbic acid), EP (epinephrine) and UA (uric acid) simultaneously. Moreover, the β-NiS@rGO/AuNS/GCE exhibits significant detection of AA by one order and UA by two orders higher sensitivity when compared to a β-NiS@rGO modified electrode. We investigated using this electrocatalyst for individual detection, the linear responses of AA, EP and UA at concentrations in the ranges of 900 nM to 100 μM, 2 μM to 1 mM and 100 nM to 1 mM with low detection limits of 331 nM, 540 nM and 4.5 nM (S/N = 3 σ / b ), respectively; the resulting non-enzymatic biosensor also retained a good response to simultaneous detection with a wide linear range 1 μM to 1 mM, 2 μM to 1 mM and 100 nM to 1 mM and significantly lower detection limits of 682 nM, 1.3 μM and 6 nM, respectively. Excellent stability, reproducibility, and selectivity were achieved. Biosensing of AA, EP and UA in human urine, blood, serum, fruits and pharmaceutical drugs was successfully demonstrated without any preliminary treatment.